2010
DOI: 10.5194/bg-7-1271-2010
|View full text |Cite
|
Sign up to set email alerts
|

Surface layer similarity in the nocturnal boundary layer: the application of Hilbert-Huang transform

Abstract: Abstract. Turbulence statistics such as flux-variance relationship are critical information in measuring and modeling ecosystem exchanges of carbon, water, energy, and momentum at the biosphere-atmosphere interface. Using a recently proposed mathematical technique, the Hilbert-Huang transform (HHT), this study highlights its possibility to quantify impacts of non-turbulent flows on turbulence statistics in the stable surface layer. The HHT is suitable for the analysis of non-stationary and intermittent data an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Compared to Fourier-based filters and wavelet decompositions, the empirical mode decomposition (EMD) is adaptive and has high locality, and therefore capable of handling some of the non-linear and non-stationary occurrences that are ubiquitous in turbulence data (Huang et al 1998, Huang andWu 2008). EMD has been favored in several atmospheric boundary layer (ABL) studies (Hong et al 2010, Barnhart et al 2012, Wang et al 2013, Gao et al 2016. The ensemble empirical mode decomposition (EEMD) (Wu and Huang 2009), a method based on EMD (Huang et al 1998, Huang andWu 2008) for time series analysis, was adopted here.…”
Section: Ensemble Empirical Mode Decomposition (Eemd)mentioning
confidence: 99%
“…Compared to Fourier-based filters and wavelet decompositions, the empirical mode decomposition (EMD) is adaptive and has high locality, and therefore capable of handling some of the non-linear and non-stationary occurrences that are ubiquitous in turbulence data (Huang et al 1998, Huang andWu 2008). EMD has been favored in several atmospheric boundary layer (ABL) studies (Hong et al 2010, Barnhart et al 2012, Wang et al 2013, Gao et al 2016. The ensemble empirical mode decomposition (EEMD) (Wu and Huang 2009), a method based on EMD (Huang et al 1998, Huang andWu 2008) for time series analysis, was adopted here.…”
Section: Ensemble Empirical Mode Decomposition (Eemd)mentioning
confidence: 99%
“…Land surface modelling of energy and carbon dioxide exchange faces specific problems on the Tibetan Plateau. Most influential is the strong diurnal cycle of the surface temperature, observed in dry conditions over bare soil or very low vegetation, leading to overestimation of surface sensible heat flux (Yang et al, 2009;Hong et al, 2010) caused by too high turbulent diffusion coefficients. Land surface models usually parameterise these coefficients by a fixed fraction between the roughness length of momentum and heat, however, Yang et al (2003) and Ma et al (2002) observed a diurnal variation of the thermal roughness length on the Tibetan Plateau.…”
Section: Problems Of Land Surface Modelling On the Tibetan Plateaumentioning
confidence: 99%
“…Land surface modelling of energy and carbon dioxide exchange faces specific problems on the Tibetan Plateau due to its high elevation and semi-arid conditions: a strong diurnal cycle of the surface temperature (Yang et al, 2009;Hong et al, 2010), a diurnal variation of the thermal roughness length observed on the Tibetan Plateau (Ma et al, 2002;Yang et al, 2003), and high bare soil evaporation in semiarid areas (e.g. Agam et al, 2004;Balsamo et al, 2011).…”
Section: Soil-vegetation-atmosphere Transfer Modelsmentioning
confidence: 99%